Hallux Valgus Deviation: Causes and Methods of Treatment - Iuliia Khamitova (Journal of Global Pharma Technology, 2016)
The purpose of this study is to test the minimally invasive method of surgical intervention with hallux valgus of the first toe in the elderly. The total number of operated and examined feet is 192 (182 in patients with bilateral valgus deviation and 10 with unilateral). The average age is 64.3±2.1 years. Overload on the first finger and the second and third metatarsal bones is completely absent after the operation, as well as overload on the first metatarsal bone (p≤0.001). The number of cases of overloads between the first finger and the first metatarsal bone in the postoperative period was halved (p≤0.05). In the proposed scheme of surgery, there is a significant improvement in the general condition of patients, in particular, biomechanical indicators of overload between different parts of the foot. After the operation, there was an increase in the longitudinal and a decrease in the transverse projection of the foot. Examination of the walking features of patients with bilateral hallux valgus showed the absence of pain after surgery, as well as a significant increase in the coefficient reflecting the rhythm of walking. This scheme of operation is simple in execution and methodology, and, at the same time, gives a positive result both in the short and long term. In addition, this operation is simple and cheap for patients compared to other methods of operations. The scheme of surgical intervention used on the head of the first metatarsal bone that we used allowed us to significantly improve the anatomical and biomechanical properties of the foot. The valgus deviation disappeared, gait parameters improved, and the load on both feet became more even. The consequence of the operation in the long term is a return to a normal lifestyle, wearing ordinary shoes, and an increase in physical activity. This type of surgery is most suitable for the elderly, as it is cheap and easy to perform, combined with a quick recovery.Key words: Hallux valgus, First toe, Metatarsal bones, Rhythmic walking, Biomechanical properties of the foot.